Tafonomia de biválvios em calcários oolíticos da formação Teresina (Bacia do Paraná, Permiano Médio, Prudentópolis, PR) - Neves, Jacqueline Peixoto; Rohn, Rosemarie; Simões, Marcello Guimarães [UNESP] (My University, 2010)
Herein, it is presented the first detailed taphonomic study on bivalve mollusk shells preserved in the oolitic limestones of the Teresina Formation (probably Kungurian-Roadian, Lower-Middle Permian) in the eastern margin of the Parana basin. The selected beds are located in two quarries (informally named PRU 1 and PRU 2) in Prudentopolis municipality (Center-South Parana State), and positioned approximately in the middle of the formation and probably in the Pinzonella illusa Zone. The PRU 1 limestone ([approximately]30 cm thick), which is partially silicified and intercalated with predominantly pelitic rocks, is classified as a bivalve oolitic grainstone. The basal contact is erosive and the top shows symmetrical ripple marks, which are draped by shale with mud cracks. There are two fining-upwards successions characterized by dense to dispersed packing of the shells, which are usually disarticulated, randomly oriented (many nested/stacked) and mixed with some Formapelitic intraclasts. Microhummocky cross-stratification occurs a little below the top of the bed. The PRU2 bed is classified as ooidbivalve rudstone[approximately] (~5 cm thick), where all shells are disarticulated and fragmented, showing dense packing. The bivalves probably inhabited a muddy substrate and were mixed (as parautochtonous and allochthonous bioclasts) with ooids during high-energy storm events, including posterior shell displacement as a result of bioturbation. Thus, the calcareous beds represent amalgamated proximal tempestites with a complex taphonomic history, strong temporal/spatial mixing of bioclasts and limited paleoecological resolution. They are a typical example of shell beds generated in a huge epeiric sea, which was not necessarily connected to the ocean and where very low depositional-slope gradient, very slow subsidence and minimum sediment accommodation space caused frequent sediment reworking by storm related processes.
Taphonomy of bivalve mollusks in oolitic limestones from Teresina Formation (Parana basin, Middle Permian, Prudentopolis, PR).